2022
DOI: 10.3389/fpubh.2022.757065
|View full text |Cite
|
Sign up to set email alerts
|

Perception of COVID-19 Testing in the Entire Population

Abstract: In the Slovak Republic, a mass testing of the entire population was performed. Estimates show that this testing cost more than 400 million EUR and thousands of euros were paid for one positively identified case. Thus, it is possible to state a high cost for such a project, which has been criticized by many parties. On the other hand, from a public health point of view, mass testing has helped fight the pandemic. Both the health and economic perspectives are important in assessing the success of a pandemic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…A wider acceptance of internet-based therapy was discussed in literature: Svärdman et al (2022) conducted a meta-analysis showing effectiveness of internet-delivered cognitive behavioral interventions. The increase in internet addiction was also detected in recent years, and its links to anxiety and depression were explored (Servidio et al, 2021;Gavurova et al, 2022).…”
Section: Current State Of Research On Depression Anxiety and Burnout ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A wider acceptance of internet-based therapy was discussed in literature: Svärdman et al (2022) conducted a meta-analysis showing effectiveness of internet-delivered cognitive behavioral interventions. The increase in internet addiction was also detected in recent years, and its links to anxiety and depression were explored (Servidio et al, 2021;Gavurova et al, 2022).…”
Section: Current State Of Research On Depression Anxiety and Burnout ...mentioning
confidence: 99%
“…However, it should be emphasized that psychometric instrument validation is the basis for methodologically rigorous research and thus needs to receive sufficient attention in the area of mental health. As it was shown that internet-related problems intertwined with depression and anxiety have become more prevalent in recent years (Servidio et al, 2021;Gavurova et al, 2022), the author also focused on topic 20 ("internet addiction"). Its relationships with other topics are elucidated with the dendrogram in Figure 5, where this topic clusters at a later stage with topics related to substance abuse, sleep problems, etc.…”
Section: Figurementioning
confidence: 99%
“…The COVID-19 pandemic [ 1 ], which paralyzed global healthcare systems via exceptional lockdowns and physical separation, has prompted the development of such digital technologies to serve a variety of healthcare needs throughout the world [ [2] , [3] , [4] ]. The set of digital technology developments has favored the coordination of large-scale operations like prediction and early diagnosis [ [5] , [6] , [7] , [8] , [9] , [10] ], population-level mass screening [ 11 , 12 ], quick contact tracing [ 13 , 14 ], vaccination and pharmaceutical supply chain management [ 15 ], telemedicine consultations [ 16 ], digital training [ 17 ] and e-commerce expansion [ 18 ]. Otherwise, digital technologies such as machine learning (ML) and deep learning (DL) has proved its efficiency in many computer-aided diagnosis systems for different disease [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%